Effect of Low Level Laser Therapy Vs Ultrasound Therapy in The Management of Temporomandibular Joint Pain Syndrome: Life Sciences-Physiotherapy - Saraswathi, K.; Nandhagopal, Koushik Kumar; Nandhini, S; Cyrus, Bernard Ebenezer; Kirupa, K.; Aishwarya, B.; Pavithra, S. (International Journal of Life Science and Pharma Research, 2024)
The temporomandibular joint is a synovial joint made up of articulating surface of the temporal bone and the head of the mandible.Patients suffering from temporomandibular joint pain syndrome will frequently have pain in the region, limitation in opening, asymmetrical jawmovements, and restricted jaw movements. The etiology is associated with several factors, including malocclusion, trauma, emotional stress,and para-functional habits, which cause excruciating pain and inflammation of the surrounding muscle, posterior fibers, and synovial fluid. Thisstudy evaluated and compared the effectiveness of low-level laser therapy (LLLT) and ultrasound therapy (UST) in managing temporomandibularjoint pain syndrome. This experimental study of pre and post-comparative types involves 30 subjects with temporomandibular joint painsyndrome who were selected from the outpatient department. This study included 30 subjects divided into two groups of each 15 by simplerandom sampling method.15 sessions each alternate day of low-level laser therapy (GROUP A) and ultrasound therapy (GROUP B) wereadministered to the affected side. Both groups received stretching exercises as a common intervention. Group A received low-level lasertherapy along with stretching exercises for 7 sessions /week/10 min. Group B received ultrasound therapy and stretching exercises for 7sessions /one weeks/10 min. On comparing the mean values of Group A & Group B on the Visual Analogue Scale Score in terms of painintensity, it shows a significant decrease in the post-test mean values in both groups, but (Group A - Low-level Laser Therapy) shows 2.33,which has the lower mean value is more effective than (Group B - Ultrasound Therapy) 3.53 at P ≤ 0.001. Hence the null Hypothesis isrejected. On comparing the pre-test and Post-test between Group A & Group B on VAS Score, Group A shows a highly significant difference inmean values at P ≤ 0. 001. Thus, we conclude that low-level laser therapy is more effective than ultrasound therapy in the management oftemporomandibular joint pain syndrome.